1968
DOI: 10.1071/bi9680529
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Aconitate Utilization by Sheep

Abstract: SummarySheep fed diets containing 3·5 and 7· 0% trans·aconitate on a dry weight basis for 5 days appeared normal and maintained normal levels of blood citrate, ketones, and aconitate, but showed large increases in urinary citrate. Calcium and magnesium levels in plasma and urine were not substantially modified. When trans-aconitate was placed in the rumen it disappeared rapidly but did not increase the concentration of rumen volatile fatty acids; blood and urinary aconitate values remained low. trans-Aconitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Citric acid is metabolized more rapidly than trans-aconitic acid by rumen microorganisms (Kennedy, 1968). Packett and Fordham (1965) also observed a rapid disappearance of itric acid from the rumen of lambs.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Citric acid is metabolized more rapidly than trans-aconitic acid by rumen microorganisms (Kennedy, 1968). Packett and Fordham (1965) also observed a rapid disappearance of itric acid from the rumen of lambs.…”
Section: Resultsmentioning
confidence: 90%
“…In K-fertilized Nordan, citric acid was present in appreciably lower concentrations than trans-aconitic or malic acids, but citric acid could also participate in complexing Mg in animals grazing both Nordan and Fairway. Citric acid is metabolized more rapidly than trans-aconitic acid by rumen microorganisms (Kennedy, 1968). Packett and Fordham (1965) also observed a rapid disappearance of citric acid from the rumen of lambs.…”
Section: Resultsmentioning
confidence: 99%
“…Blosser et al (1951) have also shown that highly significant differences in plasma citric acid occurs between animals. According to Kennedy (1968) citrate and trans-aconitate disappear rapidly from the rumen. Results from this study support this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Packett and Fordham (14) and Wright (18) found that the ruminal fermentation of citric acid in vivo and in vitro was rapid. Kennedy studied the fermentation of aconitic acid in vivo and likewise noted a rapid disappearance (11).…”
mentioning
confidence: 99%